Validity and Reliability Test of Content Creator Strategy Management - Silvia, Mimi; Irwansyah, Irwansyah (Jurnal Kajian Jurnalisme, 2023)
Content creator strategy management is a new domain in communication management. Content creator strategic communication management has the same pattern as strategic communication management carried out by public relations with three main functions, namely planning, organizing, and controlling. This study aims to develop a communication scale from previous research to evaluate content creator strategic management for 27 content creators with subcategories namely planning (11 items), organizing (3 items), and controlling (3 items) with a Likert scale of 1-7. This study tested the validity of the Pearson Product Moment Correlation with a significance value of less than 0.05 and the reliability test of this study used Cronbach’s Alpha Cronbach coefficient with a value of more than 0.84. The results showed that of the 17 statements tested, sixteen statements were declared valid. There is one statement that is stated to be invalid and not reliable regarding the level of purchase by followers. This is in accordance with previous research which states that credibility does not affect the level of purchase by followers. It can be concluded that this research can be used as an evaluation for quantitative research related to content creator strategy management which is very minimal. It is hoped that in the future, this research will also become a reference for research related to the content creator industry which is vulnerable to stress and faces many challenges.